Understanding consumer sentiments: A study on the smartwatch market in Chennai - P. Vishal; Aswathy Prakash G, (Journal of Contemporary Research in Management (JCRM), 2024)
This paper focuses on the burgeoning market for smartwatches in Chennai, a segment of portable computing devices known for their diversity in size, shape, and colour. In 2021, the global market value of smartwatches stood at USD 22.46 billion, and projections suggest a substantial increase to USD 97.52 billion by 2028. The aim of this study is to conduct a comprehensive market analysis of smartwatches within the geographical context of Chennai. To achieve this, the research adopted an empirical methodology, gathering data from a total of 203 respondents through the convenience sampling technique. The findings of the study indicate a strong market presence of smartwatches in Chennai, particularly among the younger demographic, attributed to the multiple benefits these devices offer. The analysis reveals that while the younger population has readily embraced smartwatches, there remains untapped potential among older demographics. The study concludes that for smartwatch companies to expand their market share in Chennai, innovative strategies targeting the older population are essential. This approach could lead to broader adoption across all age groups, further enhancing the market growth of smartwatches in the region.